A mini-review of human studies on cholesterol-lowering properties of probiotics - Bhagavathi Sundaram Sivamaruthi (2020)
© 2019 by the authors. Licensee MDPI, Basel, Switzerland. Cardiovascular diseases (CVD) are the major health issue of modernized society with a high mortality rate. Lifestyle, genetic makeup, and diet are some of the major influencing factors associated with CVD. The dyslipidemia is one such factor related to the development of several CVD. Many studies proved that the consumption of probiotics confers several health benefits. Several studies reported the evaluation of the cholesterol-lowering ability of probiotics (probiotics that showed positive effect in vitro and in vivo studies) in human volunteers. The current review summarizes the outcomes of human studies on the cholesterol-lowering property of probiotics. Probiotic consumption significantly improved the health status of hypercholesteremic patients by reducing the low-density lipoprotein cholesterol, total cholesterol, triglyceride levels, and increased the high-density lipoprotein cholesterol. The probiotic supplementation improved the lipid profile of diabetic patients, and obese people as well. However, not all probiotic interventions are effective against dyslipidemia. The results are controversial and depend on several factors such as probiotic strain, dose, duration of the treatment, lifestyle changes, etc. This literature survey indorses additional studies on the cholesterol-lowering property of probiotics, which could help to reduce the risk of CVD and other dyslipidemia associated health issues.